Pendidikan Seksualitas Untuk Anak Melalui Pemasaran Sosial Sebagai Salah Satu Upaya Pencegahan Child Sexual Abuse - Viciawati, Sari (Jurnal Ilmu Kesejahteraan Sosial, 2007)
Children empowerment through sex education can prevent children from sexual abuse. Sex education absolutely can be more efective for children if it is given earlier by parents. The problem is their parents often do not know what the importance of sex education. Although parents know that sex education is important, they do not want to do it because they still feel embarrassed. To fulfill the needs of parents to deliver knowledge about sex education is one of the effort to prevent child sexual abuse, a seminar had been held in this action research. After joining the seminar, there were many audiences who had will to change their all aspects of attitude. They accepted the idea which was proposed in this social marketing because they got the knowledge that sex education can prevent their children from sexual abuse. So that the feeling of embarrassment which was being a wall for them in doing sex education could be minimized.